Dystopian Nomadism in Marie Darrieussecq's Notre vie dans les forêts - Deborah Gaensbauer (Studies in 20th & 21st Century Literature, 2024)
In this speculative eco-dystopian novel portraying the destruction of a cloned woman’s psychic and corporeal integrity in tandem with environmental despoliation, implied allusions to Deleuzian notions of nomadism, rhizomes, the body without organs and becoming-animal are ubiquitous. Noticeably, however, Deleuze is never explicitly mentioned by the narrator although she makes abundant, wry references to other key works and figures in Western cultural and literary history. These sustained, unarticulated references to Deleuze cue the reader to approach the novel as a respectful parody. I propose that the parody in Notre vie dans les forêts (Our Life in the Forest) models the kind of socio-historical, evaluative function attributed to the genre by Linda Hutcheon in her analysis of parody’s capacity to inscribe a tension between the past and the present. Marie Darrieussecq’s engagement with very immediate ramifications of artificial intelligence, bioengineering, and multiple forms of environmental manipulation in the novel acknowledges the seminal influence of Deleuzian concepts. At the same time, this “monologue urgent” ‘urgent monologue,’ as she describes her novel, underscores the importance of contemporary reimagining of these concepts in a more practicable ecological mode (“Marie Darrieussecq ou le travail de langue en question(s)” ‘The Function of Language in Question(s)’ (175).
Keywords: Marie Darrieussecq; Gilles Deleuze; Félix Guattari; Linda Hutcheon; Rosi Braidotti; Eco-dystopian speculative fiction; Parody; Nomadism; Becoming-animal; Body without organs; Rhizomes; Genetic engineering; Cloning; Species extinction and de-extinction; Artificial intelligence